Fintech Potential for Remittance Transfers : A Central America Perspective - Bersch, Julia (IMF Working Papers; Working Paper, 2021)
This paper analyzes the potential for fintech to facilitate cheaper and more efficient remittances, and to enhance financial inclusion in Central America. Digital remittances remain nascent in the region, primarily reflecting behavioral inertia, small cost advantages of digital over traditional channels, and inadequate financial literacy. Through expanded alliances between traditional and fintech operators, digital remittances can further reduce transaction costs and reach those remote, low-income households in a timely and secure manner. A meaningful expansion of fintech remittances necessitates an enabling regulatory environment for digital financial services, and KYC and AML/CFT requirements proportionate to the value of transfers.